2013
DOI: 10.7205/milmed-d-12-00306
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Acute Motor and Sensory Axonal Neuropathy and Immune Thrombocytopenic Purpura

Abstract: A review of the literature revealed eleven previous cases of concurrent GBS and ITP; however, we report the first case of concurrent AMSAN and ITP. Among these cases, trends were noted to include sex, preceding infections, and cranial nerve involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…There is thus far, no known common receptor or process that has linked both GBS and ITP. However, as molecular mimicry is the underlying mechanism for both these diseases, there is a chance for both these entities to co-occur in the same patient as was the case with our patient and a few other patients in the literature 1,4 .…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…There is thus far, no known common receptor or process that has linked both GBS and ITP. However, as molecular mimicry is the underlying mechanism for both these diseases, there is a chance for both these entities to co-occur in the same patient as was the case with our patient and a few other patients in the literature 1,4 .…”
Section: Discussionsupporting
confidence: 63%
“…Gullian-Barre syndrome (GBS) is a disease in which there is typically damage to myelin surrounding peripheral nerves and typically presents as the classic ascending weakness, paresthesias, and numbness, all potentially in the setting of a preceding infection; this pattern is particularly associated with the GBS-subtype of Acute Inflammatory Demyelinating Polyradiculoneuropathy (AIDP) 1,2 . There are several other variants of GBS, one of which is Acute Motor and Sensory Axonal Neuropathy (AMSAN), which carries a worse prognosis and causes axonal injury rather than pure demyelination 1,3 . Compared to AIDP, AMSAN patients tend to progress much more quickly, have a higher chance of becoming debilitated and quadriparetic and have a longer time for recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GBS has been reported with other comorbid conditions like immune thrombocytopenic purpura (ITP). Sato et al (2005) and Ian M Ward et al (2013) reported a compilation of such cases in addition to their case of concurrent GBS and ITP [ 19 , 20 ]. GBS has also been reported with posterior reversible encephalopathy syndrome (PRES), Covid-19 infections, myasthenia gravis, nephrotic syndrome, pulmonary tuberculosis to name a few [ [21] , [22] , [23] , [24] , [25] ].…”
Section: Clinical Discussionmentioning
confidence: 99%
“…Electrophysiology studies may differentiate this subtype from the other forms of GBS. AMSAN usually presents with severe symptoms over a short period of time, and patients often experience a prolonged and incomplete recovery compared to other forms of GBS, as seen in this patient [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%